2017
DOI: 10.1371/journal.pntd.0005486
|View full text |Cite
|
Sign up to set email alerts
|

sCD163 levels as a biomarker of disease severity in leprosy and visceral leishmaniasis

Abstract: BackgroundCD163, receptor for the haptoglobin–hemoglobin complex, is expressed on monocytes/macrophages and neutrophils. A soluble form of CD163 (sCD163) has been associated with the M2 macrophage phenotype, and M2 macrophages have been shown to down-modulate inflammatory responses. In particular, previous studies have shown that M2 is closely associated with the most severe clinical presentation of leprosy (i.e. lepromatous leprosy (LL)), as well as tuberculosis. We hypothesized that sCD163 correlates with se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
3
28
0
1
Order By: Relevance
“…32 Although the frequency of CD163 + within the CD14 + population remained unaltered, Figure 2C, the soluble form, sCD163 was substantially increased Figure 2D, and negatively correlated with plasma IL-10, r = −.70, Figure 2E. Although sCD163 is considered as a marker of inflammation, 33 its increase has been associated with disease severity in VL 34 and may be attributed to the increased uptake of haem via CD163 leading to its subsequent shedding. Another putative contributor for sCD163 could be the raised levels of antileishmanial antibodies, 21 and was endorsed by its positive correlation with OD 405 of antileishmanial IgG, r = .46.…”
Section: Discussionmentioning
confidence: 97%
“…32 Although the frequency of CD163 + within the CD14 + population remained unaltered, Figure 2C, the soluble form, sCD163 was substantially increased Figure 2D, and negatively correlated with plasma IL-10, r = −.70, Figure 2E. Although sCD163 is considered as a marker of inflammation, 33 its increase has been associated with disease severity in VL 34 and may be attributed to the increased uptake of haem via CD163 leading to its subsequent shedding. Another putative contributor for sCD163 could be the raised levels of antileishmanial antibodies, 21 and was endorsed by its positive correlation with OD 405 of antileishmanial IgG, r = .46.…”
Section: Discussionmentioning
confidence: 97%
“…This receptor has been identified as an indicator of anti-inflammatory macrophages (M2 macrophages) ( Kristiansen et al, 2001 ). Silva et al (2017) demonstrated that in VL, the levels of soluble CD163 (sCD163) may serve as a biomarker for the severity of the disease in various inflammatory disorders. Its level was increased in VL patients and was directly correlated with clinical parameters of disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…In the same direction, Silva et al ( 102 ) demonstrated that the CD163s molecule was associated with the M2 macrophage phenotype, and it may be used as a biomarker of the clinical parameters of human VL severity. L. donovani also promotes the output of monocytes with a regulatory phenotype from the bone marrow that function as safe targets for the parasite ( 127 ).…”
Section: M1 and M2 Macrophages In Leishmania Infecmentioning
confidence: 94%